Management of Critical Lower Limb Ischemia in Endovascular Era: Experience from 511 Patients - Ghoneim, Baker; Elwan, Hussein; Eldaly, Waleed; Khairy, Hussein; Taha, Ahmad; Gad, Amr (International Journal of Angiology, 2014)
This study aims at the assessment of the achievability of the endovascular treatment of patients with critical limb ischemia (CLI) and the role of bypass in such patient. This is a prospective study conducted on patients with chronic atherosclerotic critical lower limb ischemia presenting to us over a period of 3 years. Patients presenting with nonsalvageable limbs requiring primary major amputation and nonatherosclerotic causes of CLI were excluded. Endovascular treatment was the first choice modality of treatment in revascularization of all patients. Open surgery was offered selectively for patient whom endovascular failed or complicated and for long TransAtlantic Inter-Society Consensus (TASC) II lesions in fit patients. This study included 511 cases of CLI, and the mean age was 64.5 years. Patients with Rutherford IV, V, and VI were 19.25, 60.5, and 19.25%, respectively. The TASC II aortoiliac lesions were as follows: A, B, C, and D in 33.7, 12,15.7, and 38.6%, respectively, and infrainguinal lesions were A, B, C, and D in 3.7, 19, 35.4, and 68.3%, respectively. A total of 78.3% of patients were treated by endovascular totally, while 16% were treated by surgery from the start, 3.7% of endovascular cases were converted to open surgery after failure of endovascular treatment, and 2% was offered hybrid treatment. Crossing of lesions by subintimal and intraluminal was 12.5 and 87.5%, respectively. Technical success in endovascular was 94%; however, we could successfully revascularize 96.8% of all CLI presented in this study by either surgery or endovascular. On 24 months follow-up, primary patency, secondary patency, and limb salvage by percutaneous transluminal angioplasty are 77.8, 84.7, and 90.7%, respectively. Revascularization by endovascular achieves high technical success and limb salvage in CLI, hence should be considered as preferred choice of treatment. However, both endovascular and surgery should not be counteracting each other and using both can revascularize 96.6% of CLI.
Keywords: critical limb ischemia; peripheral occlusive disease; peripheral angioplasty; limb salvage; survival